Evaluation of a Residential Mental Health Recovery Service in North Queensland - Heyeres, Marion; Kinchin, Irina; Whatley, Elise; Brophy, Lisa; Jago, Jon; Wintzloff, Thomas; Morton, Steve; Mosby, Vinitta; Gopalkrishnan, Narayan; Tsey, Komla (Frontiers in Public Health, 2018)
Background: Evidence shows that sub-acute mental health recovery occurs best when a person remains active within the community and fulfils meaningful and satisfying roles of their choosing. Several residential care services that incorporate these values have been established in Australia and overseas. Aims: This paper a) describes the development of an evaluation framework for a new sub-acute residential mental health recovery service in regional Australia; and b) reports on the formative evaluation outcomes based on the evaluation framework. Methods: Continuous quality improvement and participatory research approaches informed all stages of the development of the evaluation framework. A program logic was established and subsequently tested for practicability. The resultant logic utilises the Scottish Recovery Indicator 2 (SRI) service development tool, Individual Recovery Plans (IRP), and the impact assessment of the service on psychiatric inpatient admissions (reported separately). Results: Service strengths included a recovery-focused practice that identifies and addresses the basic needs of residents (consumers). The consumers of the service were encouraged to develop their own goals and self-manage their recovery plans. The staff of the service were identified as working effectively in the context of the recovery process; the staff were seen as supported and valued. Areas for improvement included more opportunities for self-management for residents and more feedback from residents and carers.